Physicochemical characteristics of flavor powder of blue swimmer crab (Portunus pelagicus) lemi with maltodextrin addition: Karakteristik fisikokimia flavor bubuk lemi rajungan (Portunus pelagicus) dengan penambahan maltodekstrin - Kusumaningrum, Indrati; Afiah, Rahmania Nur; Adhihendra, Brian Gregory (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
The blue swimmer crab is one of the most important commodities and has high economic value. High export demand is followed by an increase in the volume of by-products, namely semi-solid substances (lemi). Lemi can be used as a flavor, but the product in the market is not optimal. Fillers such as maltodextrin need to be added to improve the flavor characteristics of the powder. This study aimed to determine the best concentration of maltodextrin on the physicochemical characteristics of crab lemi powder flavor. We used a completely randomized design (CRD) to compare the effects of various maltodextrin concentrations (5%, 10%, and 15%) on the yield, cooking loss, bulk density, and proximate composition of the flavor powder. The best concentration was 10% maltodextrin with a 26.68% yield, 73.54% cooking loss, 0.58 g/mL bulk density, 3.14% moisture content, 11.60% ash, 42.40% protein, 11.69% fat, and 31.18% carbohydrate. The addition of maltodextrin to the flavored blue swimmer crab lemi powder has the potential to transform it into a powdered flavoring suitable for a variety of food types.